2002
DOI: 10.1007/s00520-002-0370-3
|View full text |Cite
|
Sign up to set email alerts
|

Supportive care provided by physicians and nurses to women with breast cancer

Abstract: Breast cancer patients' utilisation of supportive care has been understudied. In this paper, results from a population-based survey are used to assess the role of physicians and nurses in providing supportive care to women. Participants for this study were women with histologically confirmed invasive breast cancer diagnosed 23-36 months prior to contact about the study, who were randomly selected from the Ontario Cancer Registry. Patients for whom a physician approved contact were sent a survey questionnaire. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 20 publications
1
34
0
Order By: Relevance
“…An important question is whether the IM practitioner is adding factors beyond a humanistic, empowering relationship to the treatment program, a caring experience that another provider might otherwise provide in an optimal healing environment. 35,42 The notable differences in emphasis between cancer and noncancer patients in the current data with regard to patient-provider relationships (17.2% vs 51.7%) suggest that cancer patients, in contrast with noncancer patients, may value elements of IM other than the supportive provider-patient relationship, for example, the possibility of learning about new options for treatment.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…An important question is whether the IM practitioner is adding factors beyond a humanistic, empowering relationship to the treatment program, a caring experience that another provider might otherwise provide in an optimal healing environment. 35,42 The notable differences in emphasis between cancer and noncancer patients in the current data with regard to patient-provider relationships (17.2% vs 51.7%) suggest that cancer patients, in contrast with noncancer patients, may value elements of IM other than the supportive provider-patient relationship, for example, the possibility of learning about new options for treatment.…”
Section: Discussionmentioning
confidence: 77%
“…Hann also desired a "more involved" relationship with their provider yet did not report a negative experience with their conventional therapies or treatment. Similarly, Gray et al 35 reported that supportive care services and provider relationships were extremely important to patients with breast cancer. Rankin et al 36 identified doctor-patient communication as the most important aspect of psychosocial care for women with breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The study did not take into consideration the effects of patient characteristics (eg, age, sex, education, income, and disease site) on physician role, an area in which other studies have found relationships. 2,25 For the purposes of this research, it was reasoned that the role indicated by physicians would be their most common role applied to the majority of their patients.…”
Section: Discussionmentioning
confidence: 99%
“…Various proposals have been offered for dealing with this mismatch of supply and demand. 2 Canadian researchers in particular have called for delegation of some cancer care, especially survivor care, to primary care physicians. 3 An important element in promulgating such a policy is its acceptance by the primary care physicians themselves.…”
Section: Commentary: Who Should Follow Our Patients?mentioning
confidence: 99%
“…Researchers have studied the relationship between support provided by family physicians (FP), specialists, or nurses to patients and their level of coping and QoL [2,18]. A good relationship with FP was associated with lower level of distress and better patients' fighting spirit [2,19].…”
mentioning
confidence: 99%